Computational exploration of a chlorinated tetrahydroisoquinoline: Geometry, reactivity, noncovalent interactions, and molecular docking evaluation - Mouslim Messali; Gaurav Jhaa; Awad A. Alrashdi; Han-seung Lee; Savaş Kaya; Abdelaziz Sabik; Murad M.A. Abualrejal; Hassane Lgaz (Results in Physics)
1-Substituted-1,2,3,4-tetrahydroisoquinolines (THIQs) have attracted significant attention as versatile scaffolds in medicinal chemistry, owing to their diverse biological activities and potential as synthetic intermediates. Herein, comprehensive density functional theory (DFT) calculations, topological assessments, population analyses, and molecular docking of 1-(1-chloroethyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline were carried out to gain deeper insights into its structural and electronic properties. Geometry optimizations at the B3LYP/6–311 + G(d,p) level accurately reproduced key bond lengths and angles. Frontier molecular orbital (FMO) evaluation indicated a HOMO predominantly localized around the chlorinated region, suggesting a strong donor site, whereas the LUMO was centered on the ring system, suggesting a possible electrophilic substitution along the isoquinoline scaffold. Global chemical reactivity descriptors (e.g., ionization potential, electron affinity, hardness, electrophilicity) indicated a molecule of moderate kinetic stability yet with sufficient electron-donating power to engage in targeted interactions. Natural Bond Orbital (NBO) analysis revealed substantial hyperconjugative delocalization among ring-based and heteroatom-centered orbitals, while the molecular electrostatic potential (MEP) and NBO partial charges supported the conclusion that the chlorines and nitrogen bear the most negative or electron-rich sites. Nonlinear optical (NLO) parameters, including a sizable dipole moment (∼ 9.73 D) and nontrivial first hyperpolarizability, implied potential applications in optoelectronics if molecular orientation can be controlled. Electron localization (ELF/LOL) and noncovalent interaction (NCI–RDG) analyses confirmed that dispersive forces, along with localized electron density at the chlorines and the ring nitrogen, govern the compound’s packing and reactivity. Molecular docking revealed that the compound exhibited selective inhibition potential, showing significantly higher affinity towards MAO-A (ΔG = −8.5 kcal/mol) compared to MAO-B (ΔG = −6.3 kcal/mol), driven by stable interactions with key residues. These results offer an integrated view of structure, reactivity, and physical properties, guiding prospective functional derivatization of tetrahydroisoquinoline-based molecules.